2013
DOI: 10.1111/j.1600-6143.2012.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Routine Voiding Cystourethrography After Renal Transplantation

Abstract: The impact of vesicoureteral reflux (VUR) on renal allograft outcomes is debatable, with small cohort studies reporting controversial results. The objective of this retrospective study was to evaluate long-term clinical effects of early VUR in a large cohort of kidney transplant patients. Posttransplantation voiding cystourethrography was used to evaluate 646 consecutive kidney transplant recipients before discharge. The study endpoints included VUR grade, death-censored graft or patient survival, renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
4
33
1
2
Order By: Relevance
“…A study by Margreiter et al . has shown that vesicoureteral reflux has no effect on long‐term outcomes after kidney transplantation, although this study has several limitations . Owing to the difficulty to sufficiently detect vesicoureteral reflux and the disputable clinical implications, it was decided not to assess this outcome variable.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Margreiter et al . has shown that vesicoureteral reflux has no effect on long‐term outcomes after kidney transplantation, although this study has several limitations . Owing to the difficulty to sufficiently detect vesicoureteral reflux and the disputable clinical implications, it was decided not to assess this outcome variable.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Dupont et al, VUR was found in almost half of renal transplantation patients with recurrent UTIs, and patients with VUR were more prone to develop renal scarring than those without VUR [4]. On the other hand, in a recent study by Margreiter et al, 40% of 646 consecutive renal transplant recipients were diagnosed with VUR by voiding cystourethrography, and VUR did not affect the occurrence of UTIs [16]. Considering the significant influence of urinary flow abnormalities on the likelihood of AGPN development, we would strongly recommend systemic examination for VUR or urine flow obstruction at the first AGPN.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, early removal of ureteric stent is encouraged within 4 to 6 weeks post kidney transplant. Finally, renal transplant lithiasis is rather an uncommon event and the incidence is from 0.4% to 1% [33][34][35][36]. The modality for treating urinary tract calculi includes ESWL, Percutaneous nephrolithotomy (PCNL) and endoscopic laser lithotripsy.…”
Section: Discussionmentioning
confidence: 99%